Holoptelea integrifolia (Roxb.) Planch: A Review of Its Ethnobotany, Pharmacology, and Phytochemistry. (15th May 2014) - Ganie, Showkat Ahmad; Yadav, Surender Singh
Abstract : Holoptelea integrifolia (Ulmaceae) is a versatile medicinal plant used in various indigenous systems of medicine for curing routine healthcare maladies. It is traditionally used in the treatment and prevention of several ailments like leprosy, inflammation, rickets, leucoderma, scabies, rheumatism, ringworm, eczema, malaria, intestinal cancer, and chronic wounds. In vitro and in vivo pharmacological investigations on crude extracts and isolated compounds showed antibacterial, antifungal, analgesic, antioxidant, anti-inflammatory, anthelmintic, antidiabetic, antidiarrhoeal, adaptogenic, anticancer, wound healing, hepatoprotective, larvicidal, antiemetic, CNS depressant, and hypolipidemic activities. Phytochemical analysis showed the presence of terpenoids, sterols, saponins, tannins, proteins, carbohydrates, alkaloids, phenols, flavonoids, glycosides, and quinines. Numerous compounds including Holoptelin-A, Holoptelin-B, friedlin, epifriedlin, β -amyrin, stigmasterol, β -sitosterol, 1, 4-napthalenedione, betulin, betulinic acid, hexacosanol, and octacosanol have been identified and isolated from the plant species. The results of several studies indicated that H. integrifolia may be used as an effective therapeutic remedy in the prevention and treatment of various ailments. However, further studies on chemical constituents and their mechanisms in exhibiting certain biological activities are needed. In addition, study on the toxicity of the crude extracts and the compounds isolated from this plant should be assessed to ensure their eligibility to be used as source of modern medicines.